Frames of reference : - Marquardt, Janet (McGraw-Hill, 2003)
Frames of Reference develops students’ critical understanding and appreciation of art by focusing on interesting intersections among the viewpoints of patrons, artists, viewers, and critics. Thematically organized with a chronological underpinning, the text includes thought-provoking chapter topics such as "The Earth as Art," "Representations of the Gods," "Patrons and the Role of the Artist," "Utopia and Dystopia," and "Identity in Contemporary Art."